Digital Wallet Promotion Strategy Towards Customer Loyalty During Pandemic Covid'19 - Putra, Defin Shahrial; Zamrudy, Zakky; Kadir , Abdul (CV ODIS, 2021)
This study aims to determine the digital wallet promotion strategy for customer loyalty during the COVID-19 pandemic. This is because all aspects of the economy are disorganized and messy, since the covid'19 outbreak. The daily activity that has changed is the payment system, where the circulation of cash is not as much as it used to be. Non-cash payments that are now widely used by people to make transactions, and what has become a habit is digital wallets or electronic money payments via smartphone applications without the hassle of making daily transactions. In this study, because the population is unknown, the sampling technique used purposive sampling, namely a sample of 384 respondents. The analysis technique used is Structural Equation Modeling (SEM). The results showed that promotions such as giving discounts and cashback can have a good impact. In addition, a good promotional strategy will help the company attract customers. The implication of this research is that there is a need to add promotion, in addition to increasing sales results it also provides added value that will create customer loyalty.